2022
DOI: 10.3126/ajms.v13i9.44447
|View full text |Cite
|
Sign up to set email alerts
|

Perception and attitude toward online versus traditional anatomy teaching: An internet-based cross-sectional study among Indian medical students during COVID pandemic

Abstract: Background: The COVID-19 pandemic necessitated conduction of online medical education in India in both synchronized and asynchronized modes. Before the pandemic, the online teaching had very limited role in anatomy education in India. Aims and Objectives: This study was conducted to know the student’s perceptions and attitudes regarding online versus traditional anatomy teaching, the problems hindering online anatomy learning, and the areas of anatomy students enjoyed in virtual lessons. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Challenges in performing online learning are the internet connection quality and poor utilization skills in online technology support [ 14 ]. There were some typical issues usually faced by students when attending online classes, such as less intensive communication, overloaded tasks, unskillful use of technological tools, anxiety and stress (probably due to the pandemic situation), physical problems, and technophobia [ 15 , 16 ]. This difference in perspectives arose because lecturers seemed to have a difficulty in assessing students’ learning progress during online classes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenges in performing online learning are the internet connection quality and poor utilization skills in online technology support [ 14 ]. There were some typical issues usually faced by students when attending online classes, such as less intensive communication, overloaded tasks, unskillful use of technological tools, anxiety and stress (probably due to the pandemic situation), physical problems, and technophobia [ 15 , 16 ]. This difference in perspectives arose because lecturers seemed to have a difficulty in assessing students’ learning progress during online classes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kumari et al reported that a majority of students in the Medical College of Jharkhand India experienced network issues (53.89%), whereas, Sarkar et al with respondents from various universities in India reported internet difficulties experienced by 42.06% of the students. Other hindrance factors, such as personal communication skill, direct communication limitation, and other reasons can also be potential factors that are needed to be evaluated [16,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, it was reported that 68.86% [22] to 98.41% [14] of respondents agreed that traditional teaching was better than online anatomy teaching.…”
Section: Discussionmentioning
confidence: 99%
“…et al reported that a majority of students in the Medical College of Jharkhand India experienced network issues (53.89%), whereas, Sarkar et al with respondents from various universities in India reported internet di culties experienced by 42.06% of the students. Other hindrance factors, such as personal communication skill, direct communication limitation, and other reasons can also be potential factors that are needed to be evaluated[14][22][23].…”
mentioning
confidence: 99%